Methods of parental treatment as perceived by children and its relationship to family pressure among high school students in Dammam - Alghamdi, Mohammed Mordi; Mohameed, Seed Abdulatheem (Journal of Educational and Psychological Sciences, 2021)
This study aimed to reveal the relationship between the methods of parental treatment represented in (discrimination, control, dominance, fluctuation, overprotection, and normal treatment methods) as perceived by children and its relationship to family pressure among high school students in Dammam. The research used the relational descriptive approach, and the study tool was two scales, the first was to measure the methods of parental treatment (Abdul-Maqsoud, 1999) and the second, the family pressure scale for adolescents and youth (Abdul-Maqsoud, 2002), and the two scales were applied to a sample of (100 students) of high school students in Dammam. The results of this research revealed that: there was a negative correlation between the method of overprotection -in the methods of treatment of the father -and family pressure, and no statistically significant relationship between the method of overprotection -in the methods of treatment of the mother- and family pressure. Based on the results of the study, the researcher proposed a number of suggestions, the most important of which were: taking a number of important educational and advisory steps in order to confront the research problem, and carrying out some academic studies related to methods of parental treatment and family pressure.